Penggunaan LKPD Interaktif untuk Meningkatkan Minat Belajar Siswa pada Pelajaran IPAS Kelas V di Sekolah Dasar Negeri 060858 Medan - Nura, Tri Aprilianda; Nasution, Ismail Saleh; Sidabungke, Sri Siswanti M (Medan Resource Center, 2025)
This study investigates the impact of using interactive Student Worksheets (LKPD) on the learning interest of fifth-grade students in Natural and Social Sciences (IPAS) at SDN 060858 Medan. The research addresses the issue of low student interest in the IPAS subject. Employing Classroom Action Research (CAR) over two cycles, data were collected using questionnaires that measured learning interest across four indicators: enjoyment, attraction, attention, and student involvement. The findings reveal a significant improvement in learning interest, with the average score increasing from 73.41 (moderate category) to 80.07 (high category). This result indicates that interactive LKPD, characterized by engaging and student-friendly features, effectively enhances students' enthusiasm and participation in learning activities. Therefore, the implementation of interactive LKPD is concluded to be a pedagogically sound approach to fostering higher learning interest among elementary school students in IPAS.